Penerapan Model Pembelajaran Time Token untuk Meningkatkan Keterampilan Berbicara Siswa - Asnita Asnita; Ummul Khair (ESTETIK : Jurnal Bahasa Indonesia, 2020)
The current study aimed to find out whether the learning model called â€œTime Tokenâ€ could improve Indonesian speaking skill of the students from VA class at SDI Karang Anyar, Rejang Lebong. This study applied a classroom action research undertaking two cycles. Each cycle comprised four stages of activities ranging from planning, implementation, observation, to reflection. The techniques deployed to collect the data were: observation, test for exercise, and documentation. The data of test were analyzed with the means and percentages of learning results, in the meantime the analysis of observation data used teachers and studentsâ€™ observation sheets with the criteria of good, moderate, and less. The results of the present study demonstrated that studentsâ€™ speaking skill on Indonesian language lesson in VA class at SDI Karang Anyar experienced improvement after â€œTime Tokenâ€ learning model was implemented. The forgoing could be viewed from the mean of 63.7 and the classical learning mastery of 47.6%. After the implementation of â€œTime Tokenâ€ learning model, studentsâ€™ Indonesian speaking skill in the material vis-a-vis commenting on factual matters experienced improvement from cycle I to cycle II. In cycle I, the mean of studentsâ€™ speaking skill was 72.1, and it increased to 78.8 in cycle II. The learning mastery was 71.4% in cycle I and 95.2% in cycle II. The teachersâ€™ observation result in cycle I was 32.5 categorized as good, and it increased to 37.5 categorized as good. The observation result in respect of studentsâ€™ activities in cycle I was 30 categorized as moderate, and in cycle II it increased to 37 categorized as good.